2022
DOI: 10.1002/nop2.1560
|View full text |Cite
|
Sign up to set email alerts
|

Workplace violence against nursing interns and patient safety: The multiple mediation effect of professional identity and professional burnout

Abstract: Background: Most nursing interns indicated they had experienced some form of workplace violence on clinical placement, which could be linked to higher adverse events. Prior researches have examined the effects of workplace violence on patient safety, but there have been very few explorations of whether workplace violence affects patient safety through professional identity and burnout among nursing interns.The purpose of this study is to test whether professional identity and professional burnout play mediatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Exposure to news of medical malignant injury events may increase medical staff 's perception of workplace violence. And the perception of workplace violence has then been found to be negatively related to medical staff 's professional identity (19) and be positively correlated with their professional burnout (20). Moreover, an investigation has found that violence against doctors leads to a 0.6% decrease in the number of students enrolled in medicine-related majors, and the violence-related news reduces the quality of medical students too (21).…”
Section: Superficial Behavioral and Deep Psychological Outcomes Of Ex...mentioning
confidence: 99%
“…Exposure to news of medical malignant injury events may increase medical staff 's perception of workplace violence. And the perception of workplace violence has then been found to be negatively related to medical staff 's professional identity (19) and be positively correlated with their professional burnout (20). Moreover, an investigation has found that violence against doctors leads to a 0.6% decrease in the number of students enrolled in medicine-related majors, and the violence-related news reduces the quality of medical students too (21).…”
Section: Superficial Behavioral and Deep Psychological Outcomes Of Ex...mentioning
confidence: 99%
“…Burnout and job stress directly influence the quality of care nurses provide (15). Burnout syndrome has profound effects on the mental health status of healthcare workers, affecting cognitive, behavioral, and psychomotor function, which can lead to medical errors and treatment failure (16).…”
Section: Introductionmentioning
confidence: 99%
“…Cynicism can lead to decreased enthusiasm for patient care and reduced satisfaction in the nursing profession (17). It is associated with lower patient safety and more adverse events (16). Workplace violence, which is often associated with cynicism, has a direct impact on burnout and patient safety (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation